Implementation of effective blended periconception lifestyle care in a tertiary hospital in the Netherlands: a cross-sectional study on determinants and patient satisfaction - Sam Schoenmakers; Rianne MJJ van der Kleij; Lenie van Rossem; Melissa van der Windt; Régine PM Steegers-Theunissen (BMJ Open)
Objective To identify implementation determinants of blended periconception lifestyle care, and to evaluate patient satisfaction.Design Cross-sectional study.Setting The outpatient clinic of the department of Obstetrics and Gynaecology of the Erasmus MC.Participants Implementation part: counsellors providing blended periconception lifestyle care. Patient satisfaction part: women who received blended periconception lifestyle care.Methods Blended periconception lifestyle care, including face-to-face counselling and 26 weeks of lifestyle coaching via the online platform ‘Smarter Pregnancy’, was implemented between June–December 2018. The Measurement Instrument for Determinants of Innovations questionnaire was used as input for the consolidated framework for implementation research to assess determinants of implementation. To evaluate patient satisfaction, patients receiving lifestyle care filled out an evaluation questionnaire, including questions on the needs for lifestyle counselling, information provision during counselling, and motivation and lifestyle change after counselling.Primary and secondary outcome measures Identification of implementation determinants and the level of patient satisfaction.Results Facilitators were reported in the implementation domains ‘characteristics of the intervention’ and ‘characteristics of the individuals’. Barriers were in the implementation domains ‘inner setting’ and ‘implementation process’. Regarding patient satisfaction on nutrition counselling, 31% of the respondents wanted information prior to the counselling session, 22% received new information after consultation, 51% got motivated to change and 40% changed their nutritional behaviour.Conclusions A considerable number of patients improved lifestyle after counselling, although, a relatively small number wanted lifestyle counselling prior to consultation.This study underlines the importance of implementation science and the information it provides for improving the implementation process.